Qualitative and quantitative expression of VHI associated cross reactive idiotopes within IgM rheumatoid factor from patients with early synovitis. Issue 3 (March 1990) - Shokri, F; Mageed, R A; Tunn, E; Bacon, P A; Jefferis, R
Abstract : Monoclonal rheumatoid factors (RFs) of the major Wa cross reactive idiotype group have been shown to express exclusively VKIII subgroup light chains and VHI subgroup heavy chains. A VKIII associated cross reactive idiotope (CRI) (17-109), however, was shown not to be exclusively expressed on IgM paraproteins having rheumatoid factor activity or to be present at increased levels in the sera of patients with rheumatoid arthritis (RA). Three VHI associated CRIs have been defined with monoclonal antibodies and quantitative studies of their representation are reported, together with VKIII, in IgM and IgM RF isolated from the sera of patients with early synovitis, some of whom progressed to classical RA. The results show (a) the probed CRIs were expressed predominantly on IgM RF rather than on non-RF IgM; (b) 5-10% of IgM RFs from patients with classical RA expressed the CRIs, but this represented a lower proportion of IgM RFs than observed for normal individuals or patients with self limiting synovitis; (c) VKIII light chains were highly associated with IgM RFs rather than non-RF IgM (75% and 25% respectively). It is suggested that the CRIs probed are markers for germline gene encoded antibodies or sequences resulting from minimal mutation of germline genes. The lowered proportion of RFs expressing CRIs in RA may therefore be evidence of polyclonal activation or specific antigenic stimulation, or both, resulting in maturation of the RF response with recruitment of further VH genes or extensive mutation of germline genes. These studies show that monoclonal RFs are relevant models of RF produced in RA and that the repertoire of RF autoantibodies may be encompassed within a small number of CRI expressing families.